Regulation of Cardiac PKA Signaling by cAMP and Oxidants - Friederike Cuello; Friedrich W. Herberg; Konstantina Stathopoulou; Philipp Henning; Simon Diering (MDPI AG, 2021)
Pathologies, such as cancer, inflammatory and cardiac diseases are commonly associated with long-term increased production and release of reactive oxygen species referred to as oxidative stress. Thereby, protein oxidation conveys protein dysfunction and contributes to disease progression. Importantly, trials to scavenge oxidants by systemic antioxidant therapy failed. This observation supports the notion that oxidants are indispensable physiological signaling molecules that induce oxidative post-translational modifications in target proteins. In cardiac myocytes, the main driver of cardiac contractility is the activation of the β-adrenoceptor-signaling cascade leading to increased cellular cAMP production and activation of its main effector, the cAMP-dependent protein kinase (PKA). PKA-mediated phosphorylation of substrate proteins that are involved in excitation-contraction coupling are responsible for the observed positive inotropic and lusitropic effects. PKA-actions are counteracted by cellular protein phosphatases (PP) that dephosphorylate substrate proteins and thus allow the termination of PKA-signaling. Both, kinase and phosphatase are redox-sensitive and susceptible to oxidation on critical cysteine residues. Thereby, oxidation of the regulatory PKA and PP subunits is considered to regulate subcellular kinase and phosphatase localization, while intradisulfide formation of the catalytic subunits negatively impacts on catalytic activity with direct consequences on substrate (de)phosphorylation and cardiac contractile function. This review article attempts to incorporate the current perception of the functionally relevant regulation of cardiac contractility by classical cAMP-dependent signaling with the contribution of oxidant modification.